The impact of intellectual capital on business efficiency and financial success in creative SMEs - Divianto, Divianto; Kamaludin, Kamaludin; Santi, Fitri; Saiful, Saiful (Goodwood Publishing, 2024)
Purpose: This study examines the role of Intellectual Capital (IC), including Human Capital (HC), Structural Capital (SC), and Relationship Capital (RC), as moderating variables in the relationship between business efficiency and financial performance, measured by Return on Assets (ROA) and Return on Sales (ROS) in Creative Economy-based Micro, Small, and Medium Enterprises (MSMEs) in Palembang City. Method: Using financial data from MSMEs between 2020 and 2023, this study employs a quantitative approach and a survey method. The study population consisted of 1,233 MSMEs across 15 creative economy subcategories, guided by the Department of Industry and Trade of Palembang City. A total of 400 respondents were selected using Slovin's formula and purposive sampling. Data were collected through direct interviews and questionnaires and analyzed using the Panel Least Squares Method. Results: The findings reveal that Business efficiency significantly influences ROA but not ROS. Human capital enhances the impact of business efficiency on both ROA and ROS, whereas customer capital does not strengthen this relationship. Structural capital boosts the effect of business efficiency on ROA but not on ROS. Limitations: This study is confined to Palembang City and the creative economy MSME sector, necessitating cautious generalization to other regions or sectors. Future research should explore additional moderating variables beyond IC. Contribution: This study contributes to the understanding of IC's role in enhancing business efficiency and its subsequent impact on the financial performance of creative economy-based MSMEs. Novelty: This research highlights the critical importance of managing human capital and structural capital to improve financial outcomes, providing new insights into the factors influencing the performance of creative-economy MSMEs.